Quantitative intravascular biological fluorescence-ultrasound imaging of coronary and peripheral arteries in vivo - Bozhko, Dmitry; Osborn, Eric A.; Rosenthal, Amir; Verjans, Johan W.; Hara, Tetsuya; Kellnberger, Stephan; Wissmeyer, Georg; Ovsepian, Saak V.; Mccarthy, Jason R.; Mauskapf, Adam; Stein, Ashley F.; Jaffer, Farouc A.; et al. (European Heart Journal - Cardiovascular Imaging, 2017)
Aims: (i) to evaluate a novel hybrid near-infrared fluorescence - intravascular ultrasound (NIRF-IVUS) system in coronary and peripheral swine arteries in vivo; (ii) to assess simultaneous quantitative biological and morphological aspects of arterial disease. Methods and results: Two 9F/15MHz peripheral and 4.5F/40MHz coronary near-infrared fluorescence (NIRF)-IVUS catheters were engineered to enable accurate co-registrtation of biological and morphological readings simultaneously in vivo. A correction algorithm utilizing IVUS information was developed to account for the distance-related fluorescence attenuation due to through-blood imaging. Corrected NIRF (cNIRF)-IVUS was applied for in vivo imaging of angioplasty-induced vascular injury in swine peripheral arteries and experimental fibrin deposition on coronary artery stents, and of atheroma in a rabbit aorta, revealing feasibility to intravascularly assay plaque structure and inflammation. The addition of ICG-enhanced NIRF assessment improved the detection of angioplasty-induced endothelial damage compared to standalone IVUS. In addition, NIRF detection of coronary stent fibrin by in vivo cNIRF-IVUS imaging illuminated stent pathobiology that was concealed on standalone IVUS. Fluorescence reflectance imaging and microscopy of resected tissues corroborated the in vivo findings. Conclusions: Integrated cNIRF-IVUS enables simultaneous co-registered through-blood imaging of disease related morphological and biological alterations in coronary and peripheral arteries in vivo. Clinical translation of cNIRF-IVUS may significantly enhance knowledge of arterial pathobiology, leading to improvements in clinical diagnosis and prognosis, and helps to guide the development of new therapeutic approaches for arterial diseases.
CRIS-Team Scopus Importer:2023-03-08
Keywords: fluorescence imaging; IVUS; molecular imaging; NIRF